Wideband tetraskelion dielectric resonator antenna - Irfan Ali; Mohd Haizal Jamaluddin; Abinash Gaya (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this paper, a wideband tetraskelion dielectric resonator antenna with a low profile and high gain for the upcoming fifth generation (5G) communication applications is presented. The proposed DR antenna has been designed at the operating frequency of 26 GHz. The designed antenna is etched on Rogers RT/Duroid 5880 substrate of dielectric constant =2.2, with a thickness of 0.254mm. The DR material having a relative dielectric constant ( ) of 10 is used for a proposed design. The antenna was fed by using a 50-ohm microstrip line with slot coupling. The simulation and optimization have been performed by using the commercial software CST Microwave studio. The proposed structure exhibits a wide impedance bandwidth of 19.6% for |S11|< -10 dB from 24.5 to 29.6 GHz and peak gain of 9 dBi with the efficiency of 95% for complete bandwidth. The results show that an antenna is low profile and can be used for 5G wireless communication Applications.